Development of a swine RNA polymerase I driven Influenza reverse genetics system for the rescue of type A and B Influenza viruses - Seibert, Brittany (J Virol Methods, 2020)
Influenza viruses are among the most significant pathogens of humans and animals. Reverse genetics allows for the study of molecular attributes that modulate virus host range, virulence and transmission. The most common reverse genetics methods use bi-directional vectors containing a host RNA polymerase (pol) I promoter to produce virus-like RNAs and a host RNA pol II promoter to direct the synthesis of viral proteins. Given the species-dependency of the pol I promoter and virus-host interactions that influence replication of animal-origin influenza viruses in human-derived cells, we explored the potential of using the swine RNA pol I promoter (spol1) in a bi-directional vector for rescuing type A and B influenza viruses (IAV and IBV, respectively) in swine and human cells. The spol1-based bi-directional plasmid vector led to efficient rescue of IAVs of different origins (human, swine, and avian) as well as IBV in both swine- and human-origin tissue culture cells. In addition, virus rescue was successful using a recombinant bacmid containing all eight segments of a swine origin IAV. In conclusion, the spol1-based reverse genetics system is a new platform to study influenza viruses and produce swine influenza vaccines with increased transfection efficiency.